2009
DOI: 10.1163/156853009x418073
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Kindness: The Promise of Humane Education

Abstract: Although the popularity of Humane Education Programs (HEP) as a method of teaching compassion and caring for all living beings is increasing, there is a need for rigorous, methodologically sound research evaluating the effi cacy of HEP. Recent calls for the inclusion of HEP within broader humanistic, environmental, and social justice frameworks underline the importance of HEP beyond a simple "treatment of animals" model. Lack of methodological rigor in the majority of published HEP studies (e.g., absence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 17 publications
0
14
0
4
Order By: Relevance
“…Through depicting the quality/value of life, the artistic representation neutralizes the boundary between humans and wild animals, thereby channeling the common intrinsic values of life. The study also finds that the use of the artistic work of animal photographs in humane education has generated empathy, increased the perceptions of animal individuality and fostered human-animal kinship [11,40,41].…”
Section: Artistic Exploration Interdisciplinary Learning and Humanementioning
confidence: 80%
“…Through depicting the quality/value of life, the artistic representation neutralizes the boundary between humans and wild animals, thereby channeling the common intrinsic values of life. The study also finds that the use of the artistic work of animal photographs in humane education has generated empathy, increased the perceptions of animal individuality and fostered human-animal kinship [11,40,41].…”
Section: Artistic Exploration Interdisciplinary Learning and Humanementioning
confidence: 80%
“…Urgensi pendidikan manusiawi adalah mengajarkan anak-anak mengenai kebaikan kepada hewan. Hal ini mampu menghasilkan empati yang diarahkan pada manusia dan pengurangan perilaku kekerasan dan agresif (Signal & Taylor, 2009). Pada usia sekolah dasar, anak mulai berempati dengan memikirkan perasaan dari persepektif lain.…”
Section: Gambar 7 Hasil Pretest Dan Posttest Materi Kurikulum 2013unclassified
“…Over the past two decades, some studies have suggested that humane attitudes toward animals are positively correlated with empathy to humans (Daly & Morton, 2009;Preylo & Arikawa, 2008;Signal & Taylor, 2007;Taylor & Signal, 2005). Recent studies have also evidenced that HE programs are positive interventions in promoting students' humane attitudes toward the treatment of animals (Ascione, Latham, & Worthen, 1985;Cameron, 1983;Nicoll, Samuels, & Trifone, 2008) and human-directed empathy (Arbour, Signal, & Taylor, 2009;Ascione, 1992;Ascione & Weber, 1996;Fitzgerald, 1981;Paul, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The current promising findings of HE programs, however, mainly emerged from the studies of elementary school students (Arbour et al, 2009;Ascione, 1992;Sprinkle, 2008). Ascione (1992) assessed the impact of a year-long school-based HE program on first, second, fourth and fifth graders' attitudes toward the treatment of animals as well as human-directed empathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation